Canadian Adolescents’ Concerns in the Nuclear Age: Implications for Counsellors and Teachers - Harvey, C. Brian; Howell, David; Colthorpe, Paul (Canadian Journal of Counselling and Psychotherapy, 2011)
Early and middle adolescents were asked to complete a questionnaire and to be interviewed regarding their concerns about living in the Nuclear Age. The data, which support studies in the United States and the Soviet Union, suggest both that adolescents in Canada are affected by the nuclear threat and that planning for the future, a notoriously difficult activity in adolescence, is further constrained. As well, the results suggest that there are implications for educational professionals, a group which, in terms of dealing with the fear and despair adolescents experience regarding the nuclear threat, does not appear to serve a major role as either a socializing or communicating agent. Some suggestions are offered which, hopefully, will enhance both the counsellor and the teacher in dealing with the adolescents' fear and despair that accompany living in the Nuclear Age.